Model Pendampingan Melalui Kelompok Perpuluhan Dalam Meningkatkan Kemampuan Pengelolaan Diabetus Melitus di Rumah Pada Penyandang Diabetes Mellitus Type II - Rosa Delima Ekwantini (POLTEKKES KEMENKES YOGYAKARTA, 2017)
According to the Center for Data and Information PERSI (2003,) the prevalence of diabetes mellitus type II increased. WHOestimates that the global prevalence of type II diabetes will increase from 171 million in 2000 to 366 million in 2030, andIndonesia ranked fourth after the United States, China and India. Riskesdas (2013) showed that the prevalence of DM inYogyakarta in 2013 was 2.6% and the diagnosis based on the diagnosis and symptoms of 3.0%. Results of a preliminarystudy conducted by researchers obtained data on the number raised DM 2014 in Puskesmas I Gamping Sleman many as270 people. DM disease if left untreated can lead to complications or fatal complications such as coronary heart disease,kidney failure, blindness, infections due to ulcer until amputated the affected part ulcers and can lead to death. Dasawismaperpuluhan group is a group whose members consist of people or families with the same health problems who live nearby.This group is one way for fostering community participation in the health sector so that the public be aware of the healthproblems experienced thus participate in solving the problem. The purpose of this study to determine the effect throughperpuluhan group mentoring model to DM management improvement at home in persons with diabetes mellitus type II. Typeof this research is quasi experimental design with pretest-posttest design with control group. The number of samples in thisstudy were 64 respondents that were divided into 32 groups of respondents with assistance through the perpuluhan group(treatment group) and 32 respondents with assistance through Elderly Posyandu (the comparison group). Sampling usedconsecutive sampling. Data were analyzed using Mc Nemar test and Chi square. Respondents who received assistancethrough the perpuluhan group capable of managing diabetes at home as much as 25 respondents (39.06%), while thosegetting assistance through Elderly Posyandu were 14 respondents (21.89%). Respondents who received assistancethrough perpuluhan groups that are unable to manage diabetes at home as much as 7 respondents (10.94%), while thosegetting assistance through Posyandu Elderly many as 18 respondents (28.11%) p = 0.005 <0.05. It can be concluded thatmentoring activities through a perpuluhan group is more effective than assistance through Posyandu Elderly in improving theability of the management of DM at home in the DM type II patient.